Asia Pacific Report: A New Zealand nonprofit journalism model for campus-based social justice media - Robie, David (Center for Southeast Asian Social Studies (CESASS), 2018)
For nine years, the Pacific Media Centre research and publication unit at Auckland University of Technology has published journalism with an ?activist? edge to its style of reportage raising issues of social justice in New Zealand?s regional backyard. It has achieved this through partnerships with progressive sections of news media and a nonprofit model of critical and challenging assignments for postgraduate students in the context of coups, civil war, climate change, human rights, sustainable development and neo-colonialism. An earlier Pacific Scoop venture (2009-2015) has morphed into an innovative venture for the digital era, Asia Pacific Report (APR) (http://asiapacificreport.nz/), launched in January 2016. Amid the current global climate of controversy over ?fake news? and a ?war on truth? and declining credibility among some mainstream media, the APR project has demonstrated on many occasions the value of independent niche media questioning and challenging mainstream agendas. In this article, a series of case studies examines how the collective experience of citizen journalism, digital engagement and an innovative public empowerment journalism course can develop a unique online publication. The article traverses some of the region?s thorny political and social issues?including the controversial police shootings of students in Papua New Guinea in June 2016.